A pesca, processamento artesanal e qualidade microbiológica do produto final do pepino do mar Holothuria grisea Selenka, 1867 (ECHINODERMATA: HOLOTHUROIDEA) no extremo litoral Oeste do Ceará - Ponte, Isabela de Abreu Rodrigues (2017)
Invertebrate fishing has expanded worldwide and the catch of sea cucumbers has been highlighted. Brazil has, in abundance, along its coast, the species Holothuria grisea, target of the fishing in the state of Ceará, Northeast region. The present work consists of two chapter whose objectives were (a) to characterize the sea cucumber fishery, through the evaluation of productivity, identification of length classes most susceptible to capture, estimation of fishing effort employed, as well as processing Of the resource, of the bodily yield processed, characterization of the stakeholders and the income and commercialization of the final product, and (b) evaluation of hygienic-sanitary conditions in the artisanal processing and the microbiological quality of the species. To carry out the first survey, fourteen field trips were carried out for the collection of concomitant data in two communities on the west coast of Ceará, during the period from August 2015 to July 2016. For this purpose, observations were made of the entire fishing cycle For the collection of data, such as the types of vessels and fishing gear used, or materials that assist in capturing the resource, determination of the duration of the fishing activity, quantification of the total captured measured in biomass and biometry in the captured organisms. Fishing for sea cucumbers is carried out near the coast on sandstone reefs by manual catch and in submerged reefs by free diving. The artisanal processing is carried out in four stages: evisceration, cooking, draining and drying. The annual biomass exploited for the fishermen of the two communities yielded the sum of 12,341.00 kg of exploited sea cucumbers. There was no significant difference for CPUE and fishing effort between communities. The processed (dehydrated) biomass showed an average loss of 79% of the weight and 49% of the length of the body yield. It was found that 66% of the captured organisms were below the size of first sexual maturation (13 - 20 cm). In both communities there is no resource consumption, all production is marketed, characterizing fishing as an important activity for generating income in the region, although it is not a regulated activity. In order to carry out the second survey, a sampling effort of six consecutive days was applied, in each community, from June to July / 2016. For that, the hygienic-sanitary conditions of the cooking and drying structures and the routine of handling were observed. Three plots of 40 grams each of cooked and dehydrated sea cucumber were collected in both communities for the microbiological analysis of the resource by means of the quantification of coagulase positive staphylococci, the determination of the most probable number of thermotolerant coliforms, the investigation of Salmonella and Vibrio counts. Inadequate sanitary conditions at sea cucumber processing sites were recorded and, despite 8 the low infrastructure of the processing sites, all samples were within the bacteriological parameters established by the current legislation. For the Vibrio count, the presence of these marine bacteria in the dried cucumber samples was verified in 50% of the analyzed lots. Therefore, it is concluded that (a) there is a need for attention of the environmental agencies (regional and federal) to this resource that is being explored without prior research and without supervision so that adequate management measures are based on this fishery, The application of improvements in the infrastructure of the processing sites and the practice of hygienic-sanitary control by resource manipulator.